Councils' use of the RMA and LGA in coastal development decisions : towards sustainability : a thesis presented in fulfilment of the requirements for the degree of Master of Resource and Environment Planning at Massey University, Palmerston North, New Zealand - Bell, Angela Maureen (Massey University, 2009)
The Resource Management Act 1991 (RMA) gave councils a mandate and an obligation to promote sustainability. Along with this it also introduced an expectation that the environment will be better managed than previously. Evidence shows that the environment is continuing to be degraded. This is especially evident in the coastal environment where in the early 2000s there has been unprecedented development pressure. The addition of the Local Government Act in 2002 (LGA) has strengthened councils’ sustainability mandate by stipulating a sustainable development approach and supporting processes and principles. Because the RMA and LGA have a similar sustainability directive there has been a push to utilise the compatible strengths that the LGA offers to enhance the outcomes achieved through RMA decisions, therefore, integrating and aligning the LGA and RMA. This research used case studies, including interviews, to examine how councils use their RMA and LGA mandates in coastal development decisions. The research found that currently there is little integration of the LGA’s requirements and sustainability direction in RMA coastal subdivision decisions. The case study analysis showed that using the principles and processes in the LGA and also a council’s policies, strategies, and plans other than RMA documents would provide up to date policy direction and contextual information that would be useful for RMA decisions and could provide a more sustainable outcome if used. The case studies identified a significant number of barriers to achieving sustainability through the RMA, including that much of the policy direction in RMA planning documents is not considered in deliberations. A number of these barriers are also likely to reduce attempts to integrate and align the LGA and RMA, unless they are addressed.
Keywords: Resource Management Act 1991; Local Government Act 2002; Coastal subdivision; Sustainability barriers; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300900 Land, Parks and Agriculture Management::300903 Sustainable development